Congenital Visual Field Loss from a Schizencephalic Cleft Damaging Meyer's Loop. (4th July 2021) - Kinde, Benyam; Barkovich, A. James; Horton, Jonathan C.
ABSTRACT: A healthy, asymptomatic woman was referred after incidental discovery of a right superior incongruous hemianopia. Magnetic resonance imaging disclosed a schizencephalic cleft passing through Meyer's loop of the left optic radiation. The lesion may have resulted from a focal vascular accident or disruption of cortical neurogenesis during gestation.